(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study was to compare the lipid profile and oxidant/antioxidant status between pre-menopausal and post-menopausal women and to evaluate the correlations between these variables. Material and Methods: This study included 50 healthy women, of which 21 are in pre-menopausal and 29 are post-menopausal status. This study included 50 women classified as pre-menopausal, and post-menopausal. We analyzed lipid profile in serum samples and oxidative stress in RBC samples. Oxidant status was assessed by measurement of malondialdehyde, whereas antioxidant defence was evaluated by analysis of catalase and glutathione. Results: Compared to pre-menopausal women, triglycerides, total cholesterol and low-density lipoprotein-cholesterol levels were higher and high-density lipoprotein-cholesterol levels were lower in post-menopausal women. However, difference was statistically significant only for triglycerides levels. The levels of oxidant/antioxidant system members did not differ between the groups. Conclusion: Postmenopausal status is associated with dyslipidemia, however the alterations in at oxidative status level might be reduced with the use of hormone replacement therapy, or might vary inter-individually. Keywords: Menopause; oxidative stress; antioxidant; lipid profile.